Porous solid oxide composite and solid oxide battery including the same
By using porous solid oxide composites in solid oxide batteries, the problems of insufficient electrode layer structure rigidity and electron conduction path are solved, efficient gas supply and increase of the three-phase interface area are achieved, and the reaction efficiency and stability of the battery are improved.
Patent Information
- Application Number
- CN202380058529.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-13
- Filing Date
- 2023-07-25
- Publication Date
- 2025-03-25
AI Technical Summary
In existing solid oxide fuel cells and electrolytic cells, it is difficult for air electrodes and fuel electrodes to provide sufficient structural rigidity and effective electron conduction paths, resulting in insufficient gas supply and reduced three-phase interface area.
A porous solid oxide composite is used, which consists of electrode material and solid oxide electrolyte material, with mesoporous and microporous structures, which are arranged in an opal structure, and micropores connect the mesoporous, providing structural rigidity and electron conduction pathways.
Through the porous solid oxide composite, gas can be supplied smoothly and a high-area three-phase interface can be provided, improving the reaction efficiency and stability of the battery.
Smart Images

Figure CN119698703A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority of Korean Patent Application No. 10-2022-0159246 filed on November 24, 2022, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2023-0018668 filed on February 13, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates to a porous solid oxide composite and a solid oxide battery comprising the porous solid oxide composite, wherein the porous solid oxide composite provides sufficient structural rigidity of an electrode layer, enables gas to be smoothly supplied to the electrode layer, and enables the electrode layer to have an effective electron conduction path, thereby providing a high-area three-phase interface. Background Art
[0003] Solid oxide fuel cells (SOFCs) and solid oxide electrolyzers (SOECs) generate electrical energy through an electrochemical reaction of a cell (the cell is composed of an air electrode, a fuel electrode, and a solid oxide electrolyte having oxygen ion conductivity) and generate hydrogen through the reverse reaction of the solid oxide fuel cell by electrolyzing water. The cell has a structure in which an air electrode and a fuel electrode are respectively arranged at both sides of a solid oxide electrolyte having oxygen ion conductivity, wherein air and hydrogen are respectively supplied to the air electrode and the fuel electrode through a gas flow path formed on a separator to perform an electrochemical reaction to generate electricity or perform electrolysis.
[0004] The air electrode and fuel electrode where the reaction actually takes place should allow the gas to enter easily to make the reaction efficient and have high electronic conductivity and ion conductivity. In particular, the air electrode and fuel electrode should have an internal structure that transfers ions and gases to the three-phase interface (the interface where the electrolyte, electrode and gas meet) well. Summary of the invention
[0005] Technical issues
[0006] One aspect of the present disclosure provides a porous solid oxide composite that provides sufficient structural rigidity of an electrode layer, enables smooth gas supply to the electrode layer, and enables the electrode layer to have an effective electron conduction path, thereby providing a high-area three-phase interface.
[0007] Solutions to the problem
[0008] The porous solid oxide composite according to some embodiments of the present disclosure includes a composite of an electrode material and a solid oxide electrolyte material and has mesopores and micropores, wherein the mesopores are arranged in an opal structure so that each of the mesopores having a substantially spherical shape and substantially the same size is regularly arranged and densely stacked, and the micropores connect the mesopores.
[0009] The opal structure may have a structure in which four to six of the mesopores are arranged laterally to at least one of the mesopores, two to three of the mesopores are placed directly on top of at least one of the mesopores, and two to three of the mesopores are placed directly below at least one of the mesopores.
[0010] At least one of the mesopores may be connected to an adjacent one of the mesopores through at least one of the micropores, and each of the mesopores may be connected to at least three micropores.
[0011] The average pore diameter of the mesopores may be 0.3 μm to 20 μm.
[0012] Each of the mesopores may be in a substantially spherical shape, and an average diameter of each of the mesopores having the spherical shape may be 0.3 μm to 20 μm.
[0013] Each of the micropores may have a tubular shape and have an average diameter smaller than an average pore diameter of the mesopores. The average diameter of the tubular micropores may be 0.03 μm to 2 μm and the average length of the tubular micropores may be 0.05 μm to 3 μm.
[0014] The solid oxide electrolyte material may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0015] The electrode material may be an air electrode material, comprising lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide or a combination thereof.
[0016] The electrode material may be a fuel electrode material including nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), oxides thereof, or combinations thereof.
[0017] A weight ratio of the electrode material to the solid oxide electrolyte material may be 4:1 to 0.25:1.
[0018] The porous solid oxide composite may have a porosity of 30% to 50%.
[0019] According to some embodiments of the present disclosure, the method for preparing a porous solid oxide composite includes: arranging a pore former in an opal structure on a substrate so that the pore former of the opal structure corresponds to the mesopores of the porous solid oxide composite, wherein the opal structure is a structure in which a plurality of spheres having substantially the same size are regularly arranged and closely stacked; forming a connecting portion between the pore formers, wherein the shape of the connecting portion is a tubular shape so that the connecting portion corresponds to the micropores of the porous solid oxide composite; reducing the size of the pore former; filling the space between the pore formers with an electrode material and a solid oxide electrolyte material; and firing the electrode material and the solid oxide electrolyte material by heat treatment to remove the pore former and the connecting portion.
[0020] The step of arranging the pore former in the opal structure may be performed by a Langmuir-Blodgett (LB) method, a method using a template, a spin coating method, a spray coating method, or a method of forming a self-assembly after impregnation.
[0021] The pore former may include silica, carbon black, polystyrene (PS), polymethyl methacrylate (PMMA), polytetrafluoroethylene, starch, or a combination thereof.
[0022] The pore former may have a structure having the same shape and arrangement as the one of the mesopores.
[0023] The step of forming the connection portion may be performed by performing a heat treatment at 150° C. to 300° C. for 10 minutes to 30 minutes.
[0024] The step of reducing the size of the pore former may be performed using a chemical etching method or a plasma etching method.
[0025] The etching may be performed for 1 minute to 10 minutes.
[0026] The heat treatment may be performed at 800° C. to 1500° C. for 1 hour to 5 hours.
[0027] According to some embodiments, a solid oxide cell includes a solid oxide electrolyte and an air electrode and a fuel electrode respectively disposed on either side of the solid oxide electrolyte, wherein the air electrode, the fuel electrode, or both include a porous solid oxide composite comprising an electrode material and a solid oxide electrolyte material.
[0028] The porous solid oxide composite has mesopores and micropores, the mesopores are arranged in an opal structure in which each of the mesopores has a substantially spherical shape and substantially the same size and the spheres are regularly arranged and closely packed, and the micropores connect the mesopores.
[0029] The solid oxide cell may be a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
[0030] Advantageous Effects of the Invention
[0031] According to some embodiments, the porous solid oxide composite provides sufficient structural rigidity of the electrode layer, enables smooth gas supply to the electrode layer, and enables the electrode layer to have an effective electron conduction path, thereby providing a high-area three-phase interface. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and other aspects, features and other advantages of the present disclosure will be more clearly understood through the following detailed description in conjunction with the accompanying drawings.
[0033] Figure 1 is a schematic cross-sectional view of a porous solid oxide composite according to some embodiments of the present disclosure.
[0034] Figure 2 is a schematic diagram of the pore former and the connecting part.
[0035] Figure 3 This is a transmission electron microscope (TEM) photograph of the pore former and the connecting part.
[0036] Figure 4 is a schematic diagram illustrating a solid oxide fuel cell according to some embodiments of the present disclosure.
[0037] Figure 5 is a schematic diagram showing a solid oxide electrolysis cell according to some embodiments of the present disclosure. DETAILED DESCRIPTION
[0038] Hereinafter, the present embodiment will be described in detail with reference to the accompanying drawings, so that ordinary technicians in the field can practice. The drawings and descriptions are essentially considered to be illustrative and not restrictive. Throughout the specification, the same figure numerals represent the same elements. In addition, the drawings are provided only to make the embodiments disclosed in this specification easy to understand, and are not interpreted as limiting the spirit disclosed in this specification, and it should be understood that the present disclosure includes all variants, equivalents and alternatives without departing from the scope and spirit of the present disclosure. In addition, some components are exaggerated, omitted or schematically described in the drawings, and the size of each component does not necessarily represent the actual size.
[0039] In addition, unless explicitly described to the contrary, the word “comprise” and variations such as “including” or “having”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.
[0040] A porous solid oxide composite according to one aspect includes a composite of an electrode material and a solid oxide electrolyte material.
[0041] Solid oxide electrolyte materials should have high oxygen ion conductivity and low electronic conductivity.
[0042] For example, the solid oxide electrolyte material may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0043] The electrode material may include an air electrode material or a fuel electrode material.
[0044] The cathode material may include a material that reduces oxygen to oxygen ions.
[0045] For example, the air electrode material may include metal oxide particles having a perovskite crystal structure. The perovskite metal oxide may include a mixed ionic electronic conductor (MIEC) material having both ionic conductivity and electronic conductivity, and having a high oxygen diffusion coefficient and a charge exchange reaction rate coefficient, so that the oxygen reduction reaction occurs on the entire surface of the electrode, rather than just at the three-phase interface.
[0046] The perovskite type metal oxide may be represented by Chemical Formula 1.
[0047] [Chemical formula 1]
[0048] ABO 3±γ
[0049] In Chemical Formula 1, A is an element including La, Ba, Sr, Sm, Gd, Ca, or a combination thereof, B is an element including Mn, Fe, Co, Ni, Cu, Ti, Nb, Cr, Sc, or a combination thereof, and γ represents oxygen excess or oxygen deficiency. For example, γ may be in the range of 0≤γ≤0.3.
[0050] For example, the perovskite type metal oxide may be represented by Chemical Formula 2.
[0051] [Chemical formula 2]
[0052] A' 1-x A” xB'O 3±γ
[0053] In Chemical Formula 2, A' is an element including Ba, La, Sm or a combination thereof, A" is an element including Sr, Ca, Ba or a combination thereof and is different from A', B' is an element including Mn, Fe, Co, Ni, Cu, Ti, Nb, Cr, Sc or a combination thereof, 0≤x<1, and γ represents oxygen excess or oxygen deficiency.
[0054] For example, the air electrode material may include lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide, or combinations thereof.
[0055] In this case, if the solid oxide dielectric material comprises yttria-stabilized zirconia (YSZ) and the air electrode material comprises lanthanum strontium manganese oxide (LSM), the porous solid oxide composite may comprise a LSM-YSZ composite.
[0056] The fuel electrode material can electrochemically oxidize the fuel and transfer the charge.
[0057] In some embodiments, the fuel electrode material may include pure metals such as nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), or platinum (Pt), or oxides thereof.
[0058] In this case, the porous solid oxide composite can be a cermet as a combination of a fuel electrode material and a solid oxide electrolyte material. For example, when the solid oxide electrolyte material includes yttria-stabilized zirconia (YSZ) and the fuel electrode material includes nickel (Ni), the porous solid oxide composite can include Ni / YSZ cermet, or when the fuel electrode material includes ruthenium (Ru), the porous solid oxide composite can include Ru / YSZ cermet.
[0059] The weight ratio of the electrode material to the solid oxide electrolyte material may be 4: 1 to 0.25: 1, for example, 2: 1 to 0.5: 1. When the weight ratio of the electrode material to the solid oxide electrolyte material is less than 0.25, an electrical connection path may not be formed.
[0060] Figure 1 is a schematic cross-sectional view of a porous solid oxide composite according to some embodiments of the present disclosure.
[0061] Reference Figure 1 , the porous solid oxide composite 10 has mesopores 12 arranged in an opal structure and micropores 13 connecting the mesopores 12 .
[0062] In order for the solid oxide cell to work well, the electrode layer should be well supplied with external gas in a well-sealed state. Therefore, the electrode layer has a porous structure to smoothly supply gas to the three-phase interface inside it. However, when the electrode layer has an excessively high porosity, there may be a problem of reduced durability due to reduced mechanical strength, difficulty in ensuring the electronic conduction path, and reduced area of the three-phase interface. In order to control the porosity of the electrode layer, a pore former is added to the composition for the electrode layer, wherein closed pores tend to be formed. The closed pores have a shape such as a sphere without connecting adjacent pores. When the electrode layer has many closed pores, there may be a problem of cracks and expansion or deformation due to an instantaneous increase in internal pressure during polymer volatilization, wherein the closed pores are not conducive to gas supply, thereby deteriorating the effectiveness of the electrode layer as a three-phase interface (gas reaction site).
[0063] The porous solid oxide composite according to some embodiments of the present disclosure has a three-dimensional pore network structure in which mesopores arranged in an opal structure are connected by micropores, thereby ensuring excellent gas supply, electron conductivity, reaction sites, and structural rigidity.
[0064] The opal structure may have a structure in which four to six mesopores are arranged laterally to at least one mesopore, two to three mesopores are directly on top of at least one mesopore, and two to three mesopores are directly below at least one mesopore. For example, the opal structure may have a structure in which six other mesopores are laterally located to at least one mesopore in the mesopore, three other mesopores are located above at least one mesopore, and three other mesopores are located below at least one mesopore. In addition, an opal structure such as a face-centered cubic (FCC) lattice structure or a hexagonal close-packed (HCP) lattice structure may have three mesopores located on the top, six mesopores located on the side, and three mesopores located on the bottom, centered on at least one mesopore.
[0065] At least one of the mesopores may be connected to an adjacent mesopore through at least three or more (or, for example, six to twelve micropores). When a mesopore is connected to an adjacent mesopore through one or two micropores, an open pore may not be formed.
[0066] Each of the mesopores may have a substantially spherical (bead) shape, and the mesopores may be arranged at a prescribed interval and connected to adjacent mesopores through micropores. Herein, each of the micropores may have a tubular shape and have an average diameter smaller than the average pore diameter of the mesopores.
[0067] The average pore size of the mesopores may be 0.3 μm to 20 μm, for example, 1 μm to 10 μm.
[0068] The average diameter of the micropores may be 0.03 μm to 2 μm, for example 0.05 μm to 1 μm. When the micropores have an average diameter less than 0.03 μm, there may be an unstable air flow.
[0069] The average length of the micropores may be 0.05 μm to 3 μm, for example 0.05 μm to 2 μm.
[0070] The porosity of the porous solid oxide composite may be 30% to 50%, for example 35% to 45%. When the porosity of the porous solid oxide composite is less than 30%, the gas (fuel and air) required for the reaction may not be sufficiently supplied, and when the porosity is greater than 50%, the water electrolysis cell may be easily damaged due to insufficient rigidity.
[0071] According to some embodiments of the present disclosure, a method for preparing a porous solid oxide composite includes: arranging pore formers in an opal structure on a substrate; forming connecting portions between the pore formers; reducing the size of the pore formers; filling the spaces between the pore formers with electrode materials and solid oxide electrolyte materials; and removing the pore formers and the connecting portions while firing the electrode materials and the solid oxide electrolyte materials by heat treatment.
[0072] The pore former may include, for example, silica, carbon black, polystyrene (PS), polymethyl methacrylate (PMMA), polytetrafluoroethylene, starch, or a combination thereof.
[0073] The step of arranging the pore former in the opal structure may be performed, for example, by a Langmuir Blodgett (LB) method, a method using a template, a spin coating method, a spray coating method, or a method of forming a self-assembly after impregnation.
[0074] For example, after placing a pore former in an opal structure (the opal structure has a shape in which closely packed components have uniform sizes) on a substrate, when the pore former is heat-treated, spherical pores of the pore former in the opal structure are connected to each other to form a connection portion.
[0075] The heat treatment capable of forming the connection portion may be performed at 150° C. to 300° C. for 10 to 30 minutes, for example, at 200° C. to 250° C. for 10 to 20 minutes. The temperature and time of the heat treatment may be changed according to the type and size of the material. When the heat treatment temperature is less than 150° C., or the heat treatment time is less than 10 minutes, the connection (necking) may not be fully formed, and when the heat treatment temperature is greater than 300° C., or the heat treatment time is greater than 30 minutes, the pores in the pore former may be completely filled and become a film.
[0076] Figure 2is a schematic diagram of pore formers and connectors arranged in an opal structure, and Figure 3 This is a transmission electron microscope (TEM) photograph of the pore formers and the connecting parts arranged in an opal structure.
[0077] Reference Figure 2 and Figure 3 , the balls of the pore former 22 are arranged at regular intervals, and each of the balls of the pore former 22 can be connected to adjacent balls through at least three connecting parts 23. Here, the pore former 22 has a structure in which a plurality of balls having substantially the same size are regularly arranged and closely packed, wherein each of the connecting parts 23 has a tubular shape and has an average diameter smaller than that of the balls of the pore former 22.
[0078] The size of the pore formers 22 connected by the connecting parts 23 may be reduced. Due to the reduction in the size of the pore formers 22, the prepared porous solid oxide composite has a porosity greater than 70% and may not maintain structural rigidity.
[0079] The reduction in size of the pore former may be performed, for example, using a chemical etching method or a plasma etching method. For example, etching may be performed for 1 minute to 10 minutes.
[0080] The pore former and the connecting portion are removed by filling the space of the pore former with the electrode material and the solid oxide electrolyte material and then firing the electrode material and the solid oxide electrolyte material by heat treatment.
[0081] The description of the electrode material and the solid oxide electrolyte material is the same as above, so repetition is omitted.
[0082] During the firing process, when the pore former is removed at low temperature, the electrode material and the solid oxide electrolyte material are densified and formed into a composite, mesopores are formed in regions where the pore former exists, and micropores connecting the mesopores are also formed in other regions where the connector exists.
[0083] The heat treatment for firing may be performed at 800° C. to 1500° C. for 1 to 5 hours, for example, at 1250° C. to 1350° C. for 2 to 3 hours. When the heat treatment temperature is less than 800° C., or the heat treatment time is less than 1 hour, sufficient sintering may not be achieved, but when the heat treatment temperature is greater than 1500° C., or the heat treatment time is greater than 5 hours, the pores that have been generated may disappear again.
[0084] A solid oxide cell according to another aspect includes a solid oxide electrolyte, and an air electrode and a fuel electrode respectively disposed on either side of the solid oxide electrolyte.
[0085] For example, the solid oxide cell may be a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
[0086] Figure 4 : is a schematic diagram showing a case where the solid oxide cell is a solid oxide fuel cell.
[0087] Reference Figure 4 The solid oxide fuel cell 100 includes: a fuel electrode 110; an air electrode 120 disposed facing the fuel electrode 110; and an oxygen ion conductive solid oxide electrolyte 130 disposed between the fuel electrode 110 and the air electrode 120.
[0088] The solid oxide fuel cell 100 has an electrochemical reaction as shown in Reaction Formula 1, which shows that oxygen (O2) of the air electrode 120 is converted into oxygen ions (O2 - ) and a fuel electrode reaction in which the fuel (H2 or hydrocarbon) of the fuel electrode 110 reacts with oxygen ions passing through and into the electrolyte.
[0089] [Reaction 1]
[0090] Air electrode reaction: 1 / 2O2+2e - →O2 -
[0091] Fuel electrode reaction: H2+O2 - →H2O+2e -
[0092] In the air electrode 120 of the solid oxide fuel cell 100, oxygen adsorbed into the electrode surface is dispersed and moves through surface diffusion to the three-phase interface (three-phase boundary) where the solid oxide electrolyte 130, the air electrode 120 and the pores (not shown) intersect to obtain electrons to become oxygen ions, and the generated oxygen ions move toward the fuel electrode 110 through the solid oxide electrolyte 130.
[0093] In the fuel electrode 110 of the solid oxide fuel cell 100, the moving oxygen ions combine with the hydrogen in the fuel to generate water. At this time, the hydrogen releases electrons to become hydrogen ions (H + ). The released electrons move toward the air electrode 120 through a wire (not shown) to change oxygen into oxygen ions. Through this electron movement, the solid oxide fuel cell 100 can perform a battery function.
[0094] Figure 5 Schematic diagram showing a case where the solid oxide cell is a solid oxide electrolytic cell.
[0095] Reference Figure 5 The solid oxide electrolysis cell 300 includes: an air electrode 310; a fuel electrode 320 disposed facing the air electrode 310; and an oxygen ion conductive solid oxide electrolyte 330 disposed between the air electrode 310 and the fuel electrode 320.
[0096] The solid oxide electrolysis cell 300 has an electrochemical reaction as shown in Reaction Formula 2, which shows that water (H2O) at the fuel electrode 320 is converted into hydrogen (H2) and oxygen ions (O2 - ) and an air electrode reaction in which oxygen ions passing through the solid oxide electrolyte 330 are converted into oxygen (O2). This reaction is opposite to the reaction principle of a conventional fuel cell.
[0097] [Reaction 2]
[0098] Fuel electrode reaction: H2O+2e - →O2 - +H2
[0099] Air electrode reaction: O2 - →1 / 2O2+2e -
[0100] When power is applied to the solid oxide electrolysis cell 300 from the external power supply 340, the solid oxide electrolysis cell 300 is supplied with electrons from the external power supply 340. The electrons react with the water supplied to the fuel electrode 320 to generate hydrogen and oxygen ions. The hydrogen is released to the outside, and the oxygen ions pass through the electrolyte 330 to reach the air electrode 310. The oxygen ions moved to the air electrode 310 lose electrons and then become oxygen and are released to the outside. The electrons flow to the external power supply 340. Through this electron movement, the solid oxide electrolysis cell 300 can electrolyze water to form hydrogen at the fuel electrode 320 and oxygen at the air electrode 310.
[0101] Herein, the air electrodes 120 and 310, the fuel electrodes 110 and 320, or both of them include a porous solid oxide composite according to an aspect. This is the same as described above, and will not be repeatedly described.
[0102] For example, the air electrodes 120 and 310 may have a thickness of 1 μm to 100 μm or 5 μm to 50 μm.
[0103] For example, the fuel electrodes 110 and 320 may have a thickness of 1 μm to 1000 μm or 5 μm to 100 μm.
[0104] The solid oxide electrolytes 130 and 330 play a role in transporting the generated oxygen ions from the air electrodes 120 and 310 to the fuel electrodes 110 and 320 by ion conduction. The solid oxide electrolytes 130 and 330 have airtightness to prevent contact between air and the fuel electrodes 110 and 320, and also prevent the electrons generated at the fuel electrodes 110 and 320 from moving directly toward the air electrode due to high oxygen ion conductivity and low electron conductivity (high resistance, high insulation).
[0105] In addition, since the solid oxide electrolytes 130 and 330 have the air electrodes 120 and 310 and the fuel electrodes 110 and 320 on both sides thereof, which have a very large oxygen partial pressure difference, it may be necessary to maintain the aforementioned properties in a wide oxygen partial pressure region.
[0106] The materials of the solid oxide electrolytes 130 and 330 are not particularly limited as long as they are generally used in the art, and may include, for example, yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0107] For example, the solid oxide electrolytes 130 and 330 may have a thickness of 10 nm to 100 μm or 100 nm to 50 μm.
[0108] Optionally, the solid oxide cells 100 and 300 may further include a current collecting layer (not shown) including an electrical conductor located on at least one side of the air electrodes 120 and 310 (e.g., the outside of the air electrodes 120 and 310). The current collecting layer may serve as a current collector to collect electricity in the configuration of the air electrode.
[0109] The collector layer may include, for example, lanthanum cobalt oxide (LaCoO3), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), lanthanum strontium cobalt manganese oxide (LSCM), lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), or a combination thereof. The collector layer may use the materials listed above alone or in a combination of two or more, wherein these materials may be formed into a single layer or two or more layers having a stacked structure.
[0110] The solid oxide cells 100 and 300 may be manufactured by conventional methods known in various literatures in the art.
[0111] The solid oxide cells 100 and 300 may be applied to various structures, such as a cylindrical (tubular) stack, a flat tubular stack, a planar stack, and the like.
[0112] In addition, the solid oxide cells 100 and 300 may be in the form of a unit cell stack. For example, unit cells (membrane electrode assemblies (MEAs)) composed of air electrodes 120 and 310, fuel electrodes 110 and 320, and solid oxide electrolytes 130 and 330 are stacked in series, and separators electrically connected between the unit cells are provided to obtain a unit cell stack.
[0113] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0114] <Description of Reference Numerals>
[0115] 10: Porous solid oxide composites
[0116] 11: Composites of electrode materials and solid oxide electrolyte materials
[0117] 12: Mesoporous
[0118] 13: Micropores
[0119] 22: Pore-forming agent
[0120] 23: Connection
[0121] 100: Solid Oxide Fuel Cell
[0122] 110: Fuel electrode
[0123] 120: Air electrode
[0124] 130: Solid Oxide Electrolyte
[0125] 300: Solid oxide electrolysis cell
[0126] 310: Air electrode
[0127] 320: Fuel electrode
[0128] 330: Solid Oxide Electrolyte
[0129] 340: External power supply
[0130] Industrial Applicability
[0131] The present disclosure relates to a porous solid oxide composite and a solid oxide battery comprising the porous solid oxide composite, wherein the porous solid oxide composite provides sufficient structural rigidity of an electrode layer, enables smooth gas supply to the electrode layer, and enables the electrode layer to have an effective electron conduction path, thereby providing a high-area three-phase interface.
Claims
1. A porous solid oxide composite comprising: Electrode materials and solid oxide electrolyte materials, The porous solid oxide composite has mesopores arranged in an opal structure and micropores connecting the mesopores.
2. The porous solid oxide composite according to claim 1, wherein The opal structure has the following structure: four to six of the mesopores are arranged laterally beside at least one of the mesopores, two to three of the mesopores are placed directly on top of at least one of the mesopores, and two to three of the mesopores are placed directly below at least one of the mesopores.
3. The porous solid oxide composite according to claim 1, wherein At least one of the mesopores is connected to at least three of the micropores.
4. The porous solid oxide composite according to claim 1, wherein: The average pore diameter of the mesopores is 0.3 μm to 20 μm.
5. The porous solid oxide composite according to claim 1, wherein: Each of the mesopores has a spherical shape.
6. The porous solid oxide composite according to claim 5, wherein: An average diameter of each of the micropores of the spherical shape is 0.03 μm to 2 μm.
7. The porous solid oxide composite according to claim 1, wherein: Each of the micropores has a tubular shape, and has an average diameter smaller than an average pore diameter of the mesopores.
8. The porous solid oxide composite according to claim 7, wherein: The micropores of the tubular shape have an average length of 0.05 μm to 3 μm.
9. The porous solid oxide composite according to claim 1, wherein: The weight ratio of the electrode material to the solid oxide electrolyte material is 4:1 to 0.25:
1.
10. The porous solid oxide composite according to claim 1, wherein: The porous solid oxide composite has a porosity of 30% to 50%.
11. The porous solid oxide composite according to claim 1, wherein: The solid oxide electrolyte material includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
12. The porous solid oxide composite according to claim 1, wherein: The electrode material includes an air electrode material, and the air electrode material includes lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide or a combination thereof.
13. The porous solid oxide composite according to claim 1, wherein: The electrode material is a fuel electrode material, and the fuel electrode material includes nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), platinum (Pt), oxides thereof, or a combination thereof.
14. A method for preparing a porous solid oxide composite, comprising: arranging a pore former in an opal structure on a substrate; forming a connection between the pore formers; reducing the size of the pore former; filling the spaces between the pore formers with electrode materials and solid oxide electrolyte materials; as well as The electrode material and the solid oxide electrolyte material are fired by heat treatment to remove the pore former and the connecting portion.
15. The method according to claim 14, wherein: The step of arranging the pore former in the opal structure is performed by a Langmuir-Blodgett (LB) method, a method using a template, a spin coating method, a spray coating method, or a method of forming a self-assembly after impregnation.
16. The method according to claim 14, wherein: The pore former includes silica, carbon black, polystyrene (PS), polymethyl methacrylate (PMMA), polytetrafluoroethylene, starch or a combination thereof.
17. The method according to claim 14, wherein: The step of forming the connection portion includes performing a heat treatment at 150° C. to 300° C. for 10 minutes to 30 minutes.
18. The method according to claim 14, wherein: The step of reducing the size of the pore former is performed by using chemical etching or plasma etching.
19. The method according to claim 14, wherein: The heat treatment is performed at 800° C. to 1500° C. for 1 hour to 5 hours.
20. A solid oxide battery comprising: Solid oxide electrolytes; an air electrode disposed on one side of the solid oxide electrolyte; as well as a fuel electrode disposed on an opposite side of the solid oxide electrode, wherein at least one of the air electrode or the fuel electrode comprises a porous solid oxide composite, the porous solid oxide composite comprising an electrode material and a solid oxide electrolyte material, and The porous solid oxide composite has mesopores arranged in an opal structure and micropores connecting the mesopores.
21. The solid oxide battery according to claim 20, wherein: The solid oxide cell is a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
Citation Information
Patent Citations
Dispersant and composition
KR1020220159246A
SYSTEM AND METHOD FOR MONOTORING SMALL SCALE BASED ON SPACE IoT GATEWAY
KR1020230018668A